PIENSA (Program on Investigation and Education on Reproductive Health) Project: impact of advice on Peruvian women’s contraception choices - Cáceres Chú, Eduardo (2014)
Introduction: Unmet needs for contraception are high in Peru and worldwide. Proper advice from health professionals maximizes use and compliance of contraceptive methods meeting the needs of every woman. Objectives: To determine the impact and determinant factors of gynecologists’ advice for women choosing a self-administered hormonal contraceptive method, either daily pill, weekly transdermal patch or monthly vaginal ring. Design: Observational, descriptive and transversal study. Location: Lima, Piura, Chiclayo, and Trujillo, Peru. Institution: Latin Project PIENSA: Program for Research and Education on Contraceptive Health. Participants: Five hundred eighty-one women aged 18 to 40 attended by 40 gynecologists providing advice on contraception. Interventions: Standardized counseling with educational material including information on effectiveness, mechanism of action, user mode, benefits and risks as well as suitability in regards to individual needs was conducted. Main outcome measures: Original choice and final election of contraceptive method following counseling as well as factors involved. Results: Initial method choice was 57% for the pill, 15% for the vaginal ring, and 13% for transdermal patch. Following advice election was for pill 38%, vaginal ring 33%, and transdermal patch 19%. Statistically significant preference from 15% to 33% was found in vaginal ring users, and 13% to 19% for transdermal patch; p <0,005. The main reason for method’s choice was ease of use. Conclusions: Peruvian women participating in PIENSA Project initially chose the daily contraceptive pill; but this election decreased following health professional counseling. The number of women who chose transdermal patch and vaginal ring increased significantly.